2014
DOI: 10.1212/wnl.0000000000000955
|View full text |Cite
|
Sign up to set email alerts
|

Depression in context of low neuroticism is a risk factor for stroke

Abstract: Objective: Depression predicts stroke; however, meta-analyses show significant heterogeneity.We hypothesize that the risk of depression on incident stroke is conditional upon the relative contribution of vascular disease and of neuroticism in the underlying pathways to depression in a specific patient. We examined whether depression increases stroke in persons with low neuroticism and without preexisting cardiac disease.Methods: This was a population-based cohort study with 9-year follow-up (n 5 2,050; $55 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
2
7
1
Order By: Relevance
“…An obvious hypothesis is that failures of emotion and mood regulation leading to depression in LOD in subjects with normal levels of neuroticism may stem from disease processes, in particular vascular disease, affecting the same neural circuits as implicated in neuroticism. This is consistent with the vascular depression hypothesis [45,52,53,54] and with the greater amount of WMHs, particularly in frontal areas, and greater impairments in executive functions in LOD than in EOD of similar age [for reviews, see [11,12]]. In our study 14 controls and 28 patients (14 EOD; 14 LOD) had MRI scans and were rated visually on the severity of WMHs according to the Fazekas scale [55].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An obvious hypothesis is that failures of emotion and mood regulation leading to depression in LOD in subjects with normal levels of neuroticism may stem from disease processes, in particular vascular disease, affecting the same neural circuits as implicated in neuroticism. This is consistent with the vascular depression hypothesis [45,52,53,54] and with the greater amount of WMHs, particularly in frontal areas, and greater impairments in executive functions in LOD than in EOD of similar age [for reviews, see [11,12]]. In our study 14 controls and 28 patients (14 EOD; 14 LOD) had MRI scans and were rated visually on the severity of WMHs according to the Fazekas scale [55].…”
Section: Discussionsupporting
confidence: 92%
“…In a 9-year follow-up [45], depression predicted stroke. However, in persons without preexistent cardiac disease, stroke was only predicted by depression in the absence of high neuroticism.…”
Section: Discussionmentioning
confidence: 99%
“…So far there is only one study, a 9-year follow-up study of 2050 participants, Longitudinal Aging Study Amsterdam (LASA) by Marijnissen et al, which has discussed the effect of neuroticism on the relation between depression and future risk of stroke. The study concluded that older persons with depression and low level of neuroticism had a higher risk of developing stroke, thus indicating a negative interaction between depression and neuroticism in predicting future risk of CVD [19]. In contrast, our study demonstrates that there is an interaction between neuroticism and depression in predicting risk for CVD.…”
Section: Discussioncontrasting
confidence: 56%
“…However, to our knowledge, only one previous study has addressed the question of whether the effect of neuroticism on future risk of CVD differs in the presence of depression. This study, the Longitudinal Aging Study Amsterdam (LASA), reported that depression is only predictive for future stroke in the absence of high neuroticism [ 19 ]. The proposed hypothesis in LASA was that people with lower degree of neuroticism, had more vascular disease leading to incident cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…In persons without preexistent cardiac disease, depression was associated with future stroke but only in persons with low levels of neuroticism [ 94 ]. An unfavorable course of SUBD was found to be associated with smaller network sizes and higher levels of loneliness over time, especially in men and older participants [ 95 ].…”
Section: Major Findingsmentioning
confidence: 99%